Pelatihan Peningkatan Kompetensi Guru Mata Pelajaran IPS SD dalam Penggunaan Internet Berbasis Metode E-Learning Se- SD Negeri Kecamatan Ujung Batu Kabupaten Rokan Hulu - Suarman; M.Yogi Riyantama Isjoni; Mifta Rizka; Filma Alia Sari (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
In the development of the era, teachers are required to improve competence, especially in terms of learning about digital literacy. The role of teachers is very important in creating a teaching and learning process that is following the demands of revolution 4.0. In the learning process, teachers can use the internet-based e-learning method. E-learning is a learning method that utilizes web-based information technology (IT) that can be accessed remotely so that the learning done is not only glued in the classroom and within certain hours but can still be done anytime and anywhere. Ujung Batu Subdistrict Rokan Hulu has sixteen public elementary schools scattered in various from in Ujung Batu Subdistrict. Based on the observations, elementary school teachers in Ujung Batu Subdistrict still do not use the Internet to the maximum in the learning process. Teachers use limited media and learning resources. This is due to lack of information and lack of facilities The purpose of this devotion is to increase knowledge and insight into the innovation of e-learning based learning for teachers of SD Negeri Ujung Batu can be done through training activities in the application of Google meet, Google classroom and Zoom applicated. This activity was attended by 20 people in the teachers of SD Negeri Ujung Batu with the implementation method of devotion using lecture methods, questions and answers, and simulations. The results of this dedication show that (1) the trainees know the use of e-learning application Platform, (2) The trainees already have a learning class using the platform E-Learning Application, (3) The trainees have been knowledgeable e-learning used.